Peran Pecahan dan Desimal dalam Kehidupan Sehari-Hari - Rizal Hidayat; Muhammad Reyhan Rambe; Rayhan Nawawi (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2024)
Fractions and decimals are basic mathematical concepts that have an important role in various aspects of daily life. This article discusses how fractions and decimals are used in daily activities such as measuring, calculating, and carrying out financial transactions. For example, in cooking, fractions are used to measure food ingredients, while decimals often appear in weight and length measurements. In economic transactions, decimals are key in rounding numbers and calculating prices. This article also explains the importance of understanding conversions between fractions and decimals to make decision making easier, both in personal and professional contexts. By providing applicable examples, it is hoped that this discussion can increase appreciation of the role of fractions and decimals in real life and encourage deeper mastery of these concepts.